Evaluation of the Performance of Islamic Investment Funds Worldwide: A Case Study of Al Rajhi Saudi Equity Fund - Souad, Maaizia; Mostafa, Kitcheh; Souad, Tarfaya; Zakaria, Messaoudi (Journal of Ecohumanism, 2026)
This study aimed to evaluate the performance of Islamic investment funds worldwide, through a case study of the Al Rajhi Saudi Equity Fund. Using a descriptive-analytical approach, the study examined the global landscape of Islamic investment funds, analyzed their performance, and assessed the reality and performance of the Al Rajhi Saudi Equity Fund from 2020 to 2025. The study concluded that the size and assets of Islamic investment funds worldwide are significant and show notable growth. It also found that Saudi Arabia is the leading country in adopting Islamic investment funds, hosting a large number of such funds, most notably the Al Rajhi Saudi Equity Fund, which has shown consistent asset growth over the years. Furthermore, the study concluded that the Al Rajhi Saudi Equity Fund achieved good performance during the study period and recommended that Algeria pay greater attention to Islamic investment funds and benefit from the experience of the Al Rajhi Saudi Equity Fund.